Exploiting genetic diversity and gene synthesis to identify superior nitrogenase NifH protein variants to engineer N2-fixation in plants - Xi Jiang (Nature Portfolio, 2021)
Jiang et al. show that nitrogenase NifH component of Hydrogenobacter thermophilus fulfils the quantity and functional requirements to engineer efficient N2 fixation in mitochondria. This study contributes towards future efforts engineering diazotrophs in eukaryotic cells.